Tackling the issue of generalization in qualitative study: Case study of distance learning - Dzakiria, Hisham (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Sebelas Maret (UNS) Surakarta, 2007)
Qualitative case study enables us to have a thick description and understanding of the reality.This paper suggests that while qualitative studies are not generalisable in the traditional sense of the word, nor do they claim to be, they can have other redeeming features which make them highly valuable in the education community.This can be achieved by extending the power to generalise to readers or other researchers through the concept of reliability in responding to the issue of generalisability in qualitative research In doing so, this paper discussed Michael Bassey's fuzzy generalisation to explain thepower play that readers can have in generating generalisation in qualitative research.The concept of relatabiliiy has its own merits, one that is justifiable and has its own potential to be developed.This paper is based on two qualitative case study on the experiences and perspectives of a small group of distance learners as they progress through their courses at Universiti Utara Malaysia (UUM).